The Columbia Guide to Hiroshima and the Bomb. - Kort, Michael (Columbia guides to American history and cultures., 2012)
Few aspects of American military history have been as vigorously debated as Harry Truman's decision to use atomic bombs against Japan. In this carefully crafted volume, Michael Kort describes the wartime circumstances and thinking that form the context for the decision to use these weapons, surveys the major debates related to that decision, and provides a comprehensive collection of key primary source documents that illuminate the behavior of the United States and Japan during the closing days of World War II. Kort opens with a summary of the debate over Hiroshima as it has evolved since 1945.